Randomized Controlled Trials on Relaxation Training in Complementary Treatment of Mental Disorders - Krampen Günter (Journal of Psychology and Psychotherapy Research, 2017)
Objective: Evaluation of the effectiveness of progressive relaxation (PR) versus autogenic training (AT) in the complementary treatment of anxiety disorders and depressive disorders implemented at the start of outpatient psychotherapy. Method: Randomized controlled trials including unselected samples of 60 adult patients with anxiety disorders and 60 adult patients with depressive disorders. In each study, 20 patients were randomized to (A) psychotherapy only, (B) PR-introductions additional versus (C) AT-introductions additional. Outcomes were evaluated with reference to relapse, treatment readmission, and clinical scales, including two-year follow-ups. Results: Follow-ups show that there are significantly fewer relapses and readmissions in Groups B and C than in Group A. Short-term outcomes of complementarily applied PR and AT are positive in anxiety disorders, long-term outcomes are more positive for AT. Conclusions: Suggestions for the implementation of therapy in outpatients with anxiety and depressive disorders enhancing outcomes by the indication of complementary relaxation training at the start of psychotherapy are discussed.